Students perceptions of the use of English as medium of instruction - Nur Rahma Ika Afiyanti; Sartin T. Miolo; Helena Badu (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
This study aims to explore the students’ perception of the use of English as Medium of Instruction (EMI) in teaching and learning at SMA Negeri 1 Kota Gorontalo. This explorative qualitative study employed a purposive sampling method. This study involved 112 twelve-grade students from IPA, IPS, and BAHASA majors of SMA Negeri 1 Kota Gorontalo as the subjects.  This study utilized questionnaires for data collection, while the Likert Scale and Percentage Formula were performed in data analysis. The result showed that the students had positive perceptions of the three EMI types of perception: visual, auditory, and speech perception. The average results in visual, auditory, and speech perceptions were 70.96% (‘strongly agree’ category), 70.49% (‘strongly agree’ category), and 57.90% (‘agree’ category). Further study with bigger samples and different subjects is recommended since this research only focuses on students perception of the Use of EMI in Teaching and Learning at SMA Negeri 1 Kota Gorontalo.